Model for Developing MSMEs Based on Creative Economy in Blitar Regency - Dwi Wahyuni; Cahyo Tri Atmojo; Fahimul Amri (Digital Innovation : International Journal of Management, 2025)
The role of micro, small, and medium enterprises (MSMEs) is very significant for the growth of Indonesia’s economy, accounting for 99% of all business units. The development of MSMEs in Blitar Regency has experienced significant growth in terms of both the number of entrepreneurs and revenue. The objectives of this research are (1) to identify and analyze the potential of the creative economy in the development of MSMEs in Blitar Regency, (2) to formulate appropriate strategies to enhance the competitiveness and growth of MSMEs in the creative economy sector in Blitar Regency. The approach used in this research is a phenomenological qualitative approach. Data collection techniques were carried out through observation and structured interviews conducted with key informants of this study, such as MSMEs actors, local government officials from the Department of Industry and Trade, and the Cooperative Office. The data analysis technique was conducted using data triangulation with the following steps: data collection, data analysis, conclusion, and data validation. The research results show that the creative economy model used by the local government in developing MSMEs in Blitar Regency includes the utilization of ideas and creativity, strengthening MSMEs through digitalization, business mentoring, development of superior products, and connection with the people's economy. The challenges in the development of MSMEs include increasingly tight market competition both online and offline; limited access to capital; limited access to digital technology; lack of understanding of business management; limited product innovation; ineffective marketing; and business legality. The strategies implemented include enhancing digital marketing, improving product and service quality, strengthening business capital, increasing capacity and skills, utilizing technology, promoting and marketing products, and strengthening institutions and governance.